2003
DOI: 10.1007/s11745-003-1140-7
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid FA of piezophilic bacteria from the deep sea

Abstract: Phospholipid FA (PLFA) profiles were determined on four piezophilic bacteria from the deep sea: Moritella japonica DSK1, Shewanella violacea DSS12, S. benthica DB6705, and S. benthica DB21MT-2. The total concentrations of PLFA were higher in strains grown at low pressure (DSK1, 10 MPa, 27.0 mg/g dry wt cells; DSS12, 50 MPa, 24.0 mg/g), and lower in strains grown at high pressure (DB6705, 85 MPa, 1.9 mg/g; DB21MT-2, 100 MPa, 3.0 mg/g). The piezophilic bacteria were characterized by a high abundance of unsaturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Other pressure-adapted isolates from the Gammaproteobacteria that are commonly studied include Moritella japonica (419) and Photobacterium profundum (420,576), both of which are psychrophiles. M. japonica has been used as a model to examine how cell wall composition-lipid composition in particular-varies with pressure, which revealed that phospholipid fatty acid content decreases with increasing pressure (152). P. profundum grows well in marine agar 2216 at low temperature and moderate pressure, making it an easy target for laboratory studies.…”
Section: Cultivated Prokaryotes From the Dark Oceanmentioning
confidence: 99%
“…Other pressure-adapted isolates from the Gammaproteobacteria that are commonly studied include Moritella japonica (419) and Photobacterium profundum (420,576), both of which are psychrophiles. M. japonica has been used as a model to examine how cell wall composition-lipid composition in particular-varies with pressure, which revealed that phospholipid fatty acid content decreases with increasing pressure (152). P. profundum grows well in marine agar 2216 at low temperature and moderate pressure, making it an easy target for laboratory studies.…”
Section: Cultivated Prokaryotes From the Dark Oceanmentioning
confidence: 99%
“…This likely represents an upper-estimate of this parameter because the sample came from the upper MPZ and the collection method made no attempt to distinguish between non-living detritus and (DHA-rich) organismal biomass. The DHA:C content of particle-attached bacteria (θ B = 0.08 mmol mol −1 ) represents an average value derived from various culture studies on deep-sea microbes (θ B = 0.11, 0.11, 0.03; Fang et al, 2002, 2003, 2004, respectively). The DHA:C content of protistan bacterivores (θ H = 1.4 mmol mol −1 ) is an average value for the heterotrophic dinoflagellate, Oxyrrhis marina , reared on the algae Rhodomonas sp.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Polyunsaturated fatty acids (PUFAs) such as eicosapentaenoic acid (EPA; C20:5) and docosahexaenoic acid (DHA; C22:6) are commonly distributed in the membranes of deep-sea piezophiles (Fang et al 2003;Valentine and Valentine 2004). Because of the bulky conformation, incorporation of these PUFAs into the membrane is assumed to compensate for membrane packing caused by high pressure or low temperature, thus aiding higher membrane fluidity.…”
Section: Role Of Polyunsaturated Fatty Acids In Piezo-adaptationmentioning
confidence: 99%